Role of internal auditors in corporate governance - Lam, Poh Lian (2008)
As businesses get bigger and more complex, ownership becomes diversely separated from management and the demand for enhanced accountability increases. This study examines the role of internal auditors in corporate goverance and the factors that affect the effectiveness of internal auditors in Singapore.